Development of submergence tolerant rice variety through marker-assisted backcross breeding between MR219 and Swarna-Sub1 - Ahmed, Fahim (2015)
Flash floods can result in yield losses of rice up to 100% depending upon different factors of submergence prone ecosystem. In such condition, development of submergence tolerant high yielding variety is an effective and economic way for the affected farmers to grow rice successfully. Marker-assisted selection (MAS) is an effective approach than the conventional breeding for rice varietal development. In this study, a popular high yielding but susceptible to submergence, MR219 rice variety was crossed with submergence tolerant variety, Swarna-Sub1 for development of variety tolerant to submergence through MAS. Specific objectives were to introgress submergence tolerant gene, Sub1 from Swarna-Sub1 into high yielding MR219 through marker-assisted backcross breeding, to determine suitable polymorphic SSR markers for foreground and background selection, to analyze SSR markers associated with submergence in different backcross populations for recurrent parent genome (RPG) recovery, and to identify superior improved lines to develop a new submergence tolerant rice variety. Out of 381 SSR markers including Sub1 gene linked markers, 86 were found polymorphic between the two parental varieties. These markers were used to identify the genotypic segregation ratio and RPG recovery in different backcross populations. Out of 13 foreground and recombinant primers for submergence tolerance in rice, 3 polymorphic primers, namely RM8300, RM219 and RM23805 were used to identify the target gene. These markers were used as foreground and recombinant markers in F1, BC1F1, BC2F1 and BC2F2 population. From genotypic and phenotypic verification in the respective generations, the Sub1 gene was successfully introgressed into the MR219. The results revealed that the RPG recovery ratio of the best lines ranged from 77.8 to 72.3% (average 74.4%) and 78.79 to 95.5 % (average 92.62%) in BC1F1 and BC2F1 populations, respectively. Meanwhile, in the selected lines of BC2F2 population, the RPG recovery ranged from 96.2 to 93.0% (average 94.47%), that was higher than the expected RPG recovery ratio (87.5%). Among the selected homozygous lines of BC2F2 population, the best plant with gene of interest, UPM3-BC2F2-34 was selected for the development of submergence tolerant variety. Phenotypic data were taken considering 11 traits. The UPGMA (The Un-weighted Pair Group Method with Arithmetic Means) algorithm and SAHN clustering were applied to determine genetic relationships among the genotypes. The PCA analysis of 30 lines and MR219 were calculated by EIGEN and PROJ modules of NTSYS-pc and Minitab software (version 15). From yield performances evaluation of the 30 newly developed submergence tolerant lines of BC2F3 population, lines L7, L13, L24, L12, L26, L10,L30, L14, L27 and L9 comparatively had high yields and better morphological traits. From the 30 lines, more than 70% heritability values were found for plant height, days to maturity, tiller numbers per hill, panicles per hill, percentage of filled grains and days to 50% maturity. Heritability value of more than 80% was found for yield per hill, and more than 90% were for grain length, grain width and 1000-filled grain weight. In case of phenotypic coefficient of variation (PCV), the highest value was shown by number of tillers / hill (22.20 %) and followed by panicle/hill (17.56 %)) and panicle length (12.84 %) traits. Genotypic coefficient of variation (GCV) shows variation of results as in this case, number of tillers /hill (19.45%) is the highest value followed by panicle/ hill (14.84%) and panicle length (11.05%). In case of genetic advance (GA) the highest value was shown by Number of tiller / hill (35.10) of which is close to the value of panicle/hill (25.83) and panicle length (19.59). Cluster analysis based on the quantitative traits grouped these 30 improved lines and MR219 into four clusters, and 20 of the improved lines were grouped together with the recurrent parent, MR219. From this study, the newly developed improved lines, L7, L13, L24, L12, L26, L10,L30, L14, L27 and L9 are recommended for large-scale field evaluation for the release of submergence tolerance and high yielding rice variety.